2023
DOI: 10.1186/s12913-023-09200-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter-professional collaboration and associated factors among nurses and physicians in specialized public hospitals, the northwest, Ethiopia: mixed method multi-centered cross-sectional study

Abstract: Objective The study aimed to investigate inter-professional collaboration and associated factors among nurses and physicians working in referral and teaching hospitals in the Northwest and Ethiopia in 2022. Method This study used a concurrent (quantitative cross-sectional and phenomenological qualitative) design from September to October 2022. A structured, self-administered nurse-physician collaborative scale questionnaire was used to collect quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…This result is more in line with findings from international research, as demonstrated by [3], mixed method multi-centered cross-sectional study on interprofessional collaboration and related factors among physicians and nurses in specialized public hospitals in the northwest of Ethiopia. They discovered that the study was successful in giving doctors and nurses the skills and information they needed to handle challenging communication situations and promote cooperative interactions in the healthcare setting.…”
Section: Examined Participants' Attitudes Toward Cooperation and Comm...supporting
confidence: 89%
“…This result is more in line with findings from international research, as demonstrated by [3], mixed method multi-centered cross-sectional study on interprofessional collaboration and related factors among physicians and nurses in specialized public hospitals in the northwest of Ethiopia. They discovered that the study was successful in giving doctors and nurses the skills and information they needed to handle challenging communication situations and promote cooperative interactions in the healthcare setting.…”
Section: Examined Participants' Attitudes Toward Cooperation and Comm...supporting
confidence: 89%
“…Every member of the profession in IPC practice must be able to engage in interprofessional contacts since this interaction is critical to the formation of a collaborative team with the goal of assuring the quality of treatment while also contributing to seamless team cooperation [9] . Interpersonal variables have a significant impact on IPC implementation; interprofessional collaboration is twice as likely to be effective when compared to health professionals who get poor interpersonal support [10] . However, the results of this research show that IPC practices from interpersonal factors can also be influenced by other factors, such as the educational level of the respondents, most of whom were Diploma-III in Nursing (71.1%) and nurses' knowledge of IPC practices.…”
Section: Discussionmentioning
confidence: 99%
“…The inequality of the level of education and the low competence of nurses can cause nurses to be dissatisfied with work, fatigue and risk of experiencing turnover in work in health services [15] . Professional role factors in IPC practice will also run well if supported by effective, responsive and responsible way of communicating between professional health care giving [10] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Surely, the most important and sensitive issue in nurse management is to create a balance between professional and ethical performance. [ 7 ] Medical staff, especially nurses, should protect the patients’ rights and prevent both material and non-material damages, which are their moral duty In the study of Negarandeh et al ,[ 8 ] patient support programs included the actions such as informing, learning, honoring and respecting, supporting, protecting, and providing continuity of care. Ethical failure leads to challenges and consequences that will reduce patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%